Alpha‐Synuclein Oligomers and Neurofilament Light Chain Predict Phenoconversion of Pure Autonomic Failure. Issue 6 (30th April 2021) - Singer, Wolfgang; Schmeichel, Ann M.; Shahnawaz, Mohammad; Schmelzer, James D.; Sletten, David M.; Gehrking, Tonette L.; Gehrking, Jade A.; Olson, Anita D.; Suarez, Mariana D.; Misra, Pinaki P.; Soto, Claudio; Low, Phillip A.
Abstract : Objective: To explore the role of alpha‐synuclein (αSyn) oligomers and neurofilament light chain (NfL) in cerebrospinal fluid (CSF) of patients with pure autonomic failure (PAF) as markers of future phenoconversion to multiple system atrophy (MSA). Methods: Well‐characterized patients with PAF (n = 32) were enrolled between June 2016 and February 2019 at Mayo Clinic Rochester and followed prospectively with annual visits to determine future phenoconversion to MSA, Parkinson's disease (PD), or dementia with Lewy bodies (DLB). ELISA was utilized to measure NfL and protein misfolding cyclic amplification (PMCA) to detect αSyn oligomers in CSF collected at baseline. Results: Patients were followed for a median of 3.9 years. Five patients converted to MSA, 2 to PD, and 2 to DLB. NfL at baseline was elevated only in patients who later developed MSA, perfectly separating those from future PD and DLB converters as well as non‐converters. ASyn‐PMCA was positive in all but two cases (94%). The PMCA reaction was markedly different in five samples with maximum fluorescence and reaction kinetics previously described in MSA patients; all of these patients later developed MSA. Interpretation: αSyn‐PMCA is almost invariably positive in the CSF of patients with PAF establishing this condition as α‐synucleinopathy. Both NfL and the magnitude and reaction kinetics of αSyn PMCA faithfully predict which PAF patients will eventually phenoconvert to MSA. This finding has important implications not only for prognostication, but also for future trials of disease modifying therapies, allowing for differentiation of MSA from Lewy body synucleinopathies before motor symptoms develop. ANN NEUROL 2021;89:1212–1220